Race, place, and suburban policing : too close for comfort - Boyles, Andrea S., 1973- (University of California Press, 2015)
"Relying on compelling interviews from the Meacham Park neighborhood--a marginalized Black enclave located in a predominately white affluent St. Louis suburb, this book brings to life the everyday interactions of disadvantaged suburban Blacks as they faced annexation, aggressive policing, two nationally profiled shootings, and intervention from the United States Department of Justice (USDOJ)"--Provided by publisher.